Leadership Role in Promoting Inclusive Education on the importance of Practices of Educational Leadership: A Review of Critical Literature - Khan, Tariq Mahmood; Don, Yahya (International Journal of Psychosocial Rehabilitation, 2020)
Educating the majority of the student population in Pakistan was not ever before; public schools are playing a pivotal role in the building of responsible, beneficial and good servants of the nation. This paper has explored the review of critical literature on the role of educational leadership. Four organizational chores are highlighted in this study with focusing on the communicating the school goals, supervising and evaluating instruction, monitoring the students’ progress and building professional development among teachers. Leadership assignment as the major role which undertakes these tasks can be assumed of practice form, with ethical, legal, formal, informal and expansive scopes. Educational leadership in Inclusive education needs to be embedded in the standards of equity and social justice. That is the reason, it demands leadership practice to utilize their full potential in their inclusive practices.